Edukasi Hukum Kewirausahaan dan UMKM: Pengabdian - Silvester Magnus Loogman Palit; Tumian Lian Daya Purba (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid growth of micro, small, and medium enterprises (UMKM) in Papua requires legal literacy support to ensure business sustainability and access to formal financing. This community service program implemented legal entrepreneurship education at SMU YPPK Taruna Darma Kotaraja, Jayapura City, on May 12, 2023, targeting high school students as future entrepreneurs. Using participatory education methods, the program provided comprehensive understanding of business legality, Business Identification Number (NIB) procedures, and Online Single Submission (OSS) system. Results showed significant improvement in students' legal awareness, with 85% of participants demonstrating increased understanding of business establishment procedures and 78% expressing interest in legal entrepreneurship. The program addressed critical gaps in legal literacy, considering that 44 million of Indonesia's 65 million UMKM lack access to formal financing due to legality issues. Papua's MSMEs, totaling 151,470 units with only 2.7% having NIB certification, urgently need legal literacy intervention. This educational approach proves effective in preparing compliance-ready entrepreneurs while supporting Papua's 2026 export target and sustainable economic development goals.